Five new species and re-description of eight species belonging to the family Phytoseiidae (Acari: Mesostigmata) from West Bengal, India - Bhowmik, Sagarika; Karmakar, Krishna (Zootaxa, 2021)
This paper reports on 13 species of Phytoseiidae (Acari: Mesostigmata) from West Bengal, India. Eight species, namely Euseius alstoniae (Gupta, 1975), Paraphytoseius orientalis (Narayanan, Kaur & Ghai, 1960), Amblyseiulella heveae (Oudemans, 1930), Gynaeseius ricini (Ghai & Menon, 1969), Neoseiulus longispinosus (Evans, 1952), Neoseiulus imbricatus (Corpuz & Rimando, 1966), Neoseiulus barkeri Hughes, 1948 and Phytoseius kapuri Gupta, 1969 are re-described, and five species, Typhlodromips jhilimiliensis sp. nov, Typhlodromips neosyzygii sp. nov, Proprioseiopsis amari sp. nov, Typhlodromus (Anthoseius) bolpurensis sp. nov, and Phytoseius mauritiana sp. nov. are described as new. Neoseiulus barkeri Hughes, 1948 is reported from India for the first time.